EVALUASI SISTEM PROTEKSI DALAM UPAYA PENCEGAHAN BAHAYA KEBAKARAN PADA BANGUNAN GEDUNG BADAN PENANGGULANGAN BENCANA ACEH - Winardi Aramiko; Mochammad Afifuddin; Abdul Munir (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2021)
The Aceh Disaster Management Agency office is a government office that provides services to the community in implementing disaster management activities in a planned, integrated and comprehensive manner in the pre-disaster, emergency response and post-disaster stages. One of the important things in preventing fire hazards is an emergency response plan, namely taking the form of action in the event of a fire emergency or "Emergency Response" as well as the provision of adequate fire fighting equipment for fire prevention as an effort to prevent people, buildings and their environment from being avoided. wider fire hazard. Seeing the importance of fire handling measures in the office building, it is necessary to conduct an “Emergency Response” assessment with the appropriate standards. The methodology used is the mix method combining qualitative and quantitative data with data collection, namely using secondary data in the form of a Banda Aceh City Map, BPBA Office Building Layout, literature, Permen PU, journals related to this research and primary data consisting of observations of conditions BPBA office, interview and questionnaire. The respondents used are all employees who work in the BPBA office totaling 115 people with a pilot study of 30 people. From the analysis of research data on 26 (twenty six) variables, there are 7 (seven) variables that score small or poorly and it can be interpreted that those variables need attention to make changes. A strategy that can be carried out based on the SWOT analysis is to form a fire preparedness team that is equipped with education and training in an integrated and comprehensive plan; prepare Standard Operating Procedures (SOP) for fire disaster management based on statutory regulations; perform routine and continuous building fire simulations; and strengthening other active protection systems, including making water hydrants, fire alarms and smoke detectors.